THE APPLICABILITY OF MOLECULAR HYDROGEN IN THE TREATMENT OF NEURODEGENERATIVE DISEASES: A BIBLIOGRAPHICAL REVIEW - Rodrigues Junior, Edis; Oliveira de Toledo, Juliana (Health and Society, 2025)
Introduction: This article discusses the growing research on the use of molecular hydrogen (H2) in the treatment of neurodegenerative diseases, such as Alzheimer’s, Parkinson’s and Amyotrophic Lateral Sclerosis (ALS). H2 stands out for its antioxidant and anti-inflammatory properties, which can reduce oxidative stress and inflammation in the brain, key factors in the progression of these diseases. Objective: To review current studies on the applicability of molecular hydrogen as a neuroprotective therapy, exploring its effects and possible benefits in the treatment of neurodegenerative diseases. Methodology: A literature review was carried out based on scientific articles published in the last 10 years in the PubMed, Scielo and ScienceDirect databases. Inclusion criteria included clinical and preclinical studies investigating molecular hydrogen as a therapeutic agent. Discussion: Studies indicate that H2 can act in the neutralization of free radicals, modulation of the cellular redox state and reduction of inflammation, which contributes to neuroprotection. Several administration methods are analyzed, such as inhalation, H2-enriched water, and injections. Clinical trials suggest improvements in cognitive function and reduction in the progression of neurodegenerative diseases, but research is still needed to establish optimal doses and more detailed mechanisms of action. Conclusion: Molecular hydrogen has great therapeutic potential for neurodegenerative diseases, being safe and low-cost. However, more clinical studies are needed to validate its efficacy and define treatment protocols.